Effects of Architectural and Urban Design Project Competitions on Built Environment and New Discourses Brought Thereby - OSMAN UMIT Sirel; AYSE SIREL; BURAK TURSOY (Journal of Contemporary Urban Affairs, 2019)
The competition system is considered to be the most objective project selection method in a country’s architectural and urbanism organization and is a mechanism which promotes professional creativity. Both national and international competitions have significant potential in terms of providing knowledge and accumulation to contemporary architecture history. The aim of competitions is to obtain "the best project" for a building or building group or a specific area, designs of which are predetermined. Type, nature, objective, issues, expectations of design competitions and the benefits they provide to the built environment are discussed in the general sense in this study. In this context the buildings which have been built by competitions and which are known as the important examples of the architectural history of Turkey and the world have been examined by taking into consideration their periods.  Furthermore, it has been stated that competitions are one of the methods to obtain qualified buildings and environments in Turkey, there are problems in their being sufficiently developing, leading and raising awareness. The reasons why there are still a few qualified buildings (besides exceptions) have been stressed. Recommendations as to institutions organizing design competitions, creation of specifications for design competitions and establishment of the jury in design competitions have been offered for eliminating issues in design competitions.